ETHNOOCEANOGRAPHY DAN TITIK TEMU ASPEK SYAR’I DALAM PENENTUAN AWAL BULAN RAMADHAN DAN SYAWAL OLEH JOGURU KESULTANAN TIDORE - Salnuddin, Salnuddin; Nurjaya, I Wayan; Jaya, Indra; Natih, Nyoman M.N (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2017)
Ethnooceanography and the intersection of shar'i aspects to determination of the early of Ramadan and Shawwal by Joguru Sultanate of Tidore. The determination of the early of the new month of Ramadan and Shawwal was very important for Muslims because it is related to the time of worship. Judge syara 'The Sultanate of Tidore (Joguru) has long applied the method of determining the early month of Hijri (Ramadan and Shawwal) through tidal movement observed on